Planning an Online Assessment Course for English Language Teachers in Latin America - Frank Giraldo; Xun Yan (Profile: Issues in Teachers' Professional Development)
In this article, we report the results of a study through which we collected English language teachers’ needs and wants to design an online language assessment course. Through a mixed-methods approach, we asked 20 teachers from four Latin American countries what they wanted to learn in the course. The teachers wanted a course in which they could address the challenges they faced in assessment; discuss and develop new ways to assess; and learn about authentic, valid, and ethical assessment. Therefore, the findings suggest that the teachers wanted a course that mixed theory, practice, and principles of assessment. Additionally, the course should address emerging topics in English language assessment, namely bilingual assessment and the assessment of learners with special educational needs.